CRISPR/Cas9‐mediated mutagenesis to validate the synergy between PARP1 inhibition and chemotherapy in BRCA1‐mutated breast cancer cells - Rachel L. Mintz; Yeh‐Hsing Lao; Chun‐Wei Chi; Siyu He; Mingqiang Li; Chai Hoon Quek; Dan Shao; Boyuan Chen; Jing Han; Sihong Wang; Kam W. Leong (Wiley, 2020)
Abstract For patients carrying BRCA1 mutations, at least one‐third develop triple negative breast cancer (TNBC). Not only is TNBC difficult to treat due to the lack of molecular target receptors, but BRCA1 mutations (BRCA1m) also result in chemotherapeutic resistance, making disease recurrence more likely. Although BRCA1m are highly heterogeneous and therefore difficult to target, BRCA1 gene's synthetic lethal pair, PARP1, is conserved in BRCA1m cancer cells. Therefore, we hypothesize that targeting PARP1 might be a fruitful direction to sensitize BRCA1m cancer cells to chemotherapy. We used CRISPR/Cas9 technology to generate PARP1 deficiency in two TNBC cell lines, MDA‐MB‐231 (BRCA1 wild‐type) and MDA‐MB‐436 (BRCA1m). We explored whether this PARP1 disruption (PARP1m) could significantly lower the chemotherapeutic dose necessary to achieve therapeutic efficacy in both a 2D and 3D tumor‐on‐a‐chip model. With both BRCA1m and PARP1m, the TNBC cells were more sensitive to three representative chemotherapeutic breast cancer drugs, doxorubicin, gemcitabine and docetaxel, compared with the PARP1 wild‐type counterpart in the 2D culture environment. However, PARP1m did not result in this synergy in the 3D tumor‐on‐a‐chip model, suggesting that drug dosing in the tumor microenvironment may influence the synergy. Taken together, our results highlight a discrepancy in the efficacy of the combination of PARP1 inhibition and chemotherapy for TNBC treatment, which should be clarified to justify further clinical testing.